2022
DOI: 10.1044/2021_aja-21-00148
|View full text |Cite
|
Sign up to set email alerts
|

Professional Guidelines and Reported Practice of Audiologists Performing Fall Risk Assessment With Older Adults: A Systematic Review

Abstract: Purpose: This systematic review aimed to explore the recommended fall risk assessment practices in audiology, identify audiologists' reported practices in fall risk assessment, and recognize the barriers and facilitators affecting fall risk assessment in clinical practice. Method: This systematic review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Results: CINAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Specifically, right ear processing is significantly more efficient for speech stimuli 7 . In recent years, a growing body of evidence has suggested that hearing cues contribute to balance 8,9 . Studies show that auditory information can be integrated with vestibular, somatosensory, and visual signals to improve balance, orientation, and gait [10][11][12][13] .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, right ear processing is significantly more efficient for speech stimuli 7 . In recent years, a growing body of evidence has suggested that hearing cues contribute to balance 8,9 . Studies show that auditory information can be integrated with vestibular, somatosensory, and visual signals to improve balance, orientation, and gait [10][11][12][13] .…”
mentioning
confidence: 99%
“…One of the first signs of hearing deterioration is difficulty in understanding speech in challenging everyday listening situations [15][16][17][18][19] . However, very little is known about the interaction between the deterioration of speech perception and balance.Falling and its consequences have a significant impact on individuals (loss of quality of life, nursing home admissions) and society (healthcare costs) 9,13 . Early detection of balance disorders and possible interventions can potentially reduce falling and prevent its consequences 13 .…”
mentioning
confidence: 99%
See 3 more Smart Citations